Avoiding the cost of your conscience: Belief dependent preferences and information acquisition / Claire Rimbaud, Alice Soldà - Claire Rimbaud; Alice Soldà (University of Heidelberg, Department of Economics, 2021)
Pro-social individuals face a trade-off between their monetary and moral motives. Hence, they may be tempted to exploit the uncertainty in their decision environment in order to reconcile this trade-off. In this paper, we investigate whether individuals with belief-dependent preferences avoid the monetary cost of behaving according to their moral standards by strategically acquiring information about others' expectations. We test the predictions of an information acquisition model in an online experiment. We use a modified trust-game in which we introduce uncertainty about the second movers' beliefs about first-movers' expectations. Our design enables to (i) identify participants with belief-based preferences and (ii) investigate their information acquisition strategy. Consistent with our predictions of subjective preferences, we find that most individuals classified as belief-dependent strategically select their source of information to avoid the cost of their conscience.
urn:nbn:de:bsz:16-heidok-304437
Keywords: C91; 330; Belief-dependent preferences; illusory preferences; information acquisition; self-serving biases; experiment